Effects of acidic beverages on color stability of Bulk-fill composites with different viscosities = Efectos de las bebidas ácidas sobre la estabilidad del color de resinas tipo Bulk con diferentes viscosidades - Şişmanoğlu, Soner; Sengez, Görkem (2022)
The aim of this in vitro study is to investigate the effects of acidic beverages on the discoloration of bulk-fill composites with different viscosities. 144 disc-shaped specimens (8mm diameter × 2mm thick) were prepared from four different composite resins including a nanohybrid (Filtek Ultimate), two packable bulk-fill (Filtek Bulk Fill, Tetric N Ceram Bulk Fill), and a flowable bulk-fill composite (Tetric N Flow Bulk Fill). The specimens of each group were divided into 3 subgroups and submerged in distilled water, orange juice and coke (n=12). Color difference (ΔE) were measured using CIELab color space and a compact spectrophotometer (VITA Easyshade) at baseline and after 30 days of immersion. Data were analyzed using two-way ANOVA and Tukey's HSD post-hoc tests (P<0.05). Two-way ANOVA revealed that both material type and staining solution significantly influenced ΔE values (P<0.001). Immersion in orange juice resulted in greater and significant discoloration over time in comparison to distilled water and coke (P<0.05). Tetric N Ceram (ΔE=7.0) and Tetric N Flow (ΔE=7.7) bulk-fill restoratives showed highest color change values after 30 days of immersion in orange juice. This study suggests that a discoloration above the clinically acceptable threshold (ΔE>2.7) was observed for all bulk-fill composites tested. It can be speculated that orange juice has a more negative effect on the color stability compared to coke. Additionally, flowable bulk-fill composite was more prone to discoloration than condensable bulk-fill composites.
El objetivo de este estudio fue investigar los efectos de las bebidas ácidas en la decoloración de resinas compuestas tipo Bulk con diferentes viscosidades. Se prepararon 144 muestras en forma de disco (8mm de diámetro x 2mm de grosor) a partir de cuatro resinas compuestas diferentes que incluyen un nanohíbrido (Filtek Ultimate), dos de pasta condensables tipo Bulk (Filtek Bulk Fill, Tetric N Ceram Bulk Fill) y una fluida (Tetric N Flow Bulk Fill). Las muestras de cada grupo se dividieron en 3 subgrupos y se sumergieron en agua destilada, jugo de naranja y Coca-Cola (n=12). La diferencia de color (ΔE) se midió utilizando el CIELab y un espectrofotómetro compacto (VITA Easyshade) al inicio y después de 30 días de inmersión. Los datos se analizaron mediante ANOVA bidireccional y pruebas post-hoc HSD de Tukey (P<0,05). El ANOVA bidireccional reveló que tanto el tipo de material como la solución de tinción influyeron significativamente en los valores de ΔE (P<0,001). La inmersión en jugo de naranja resultó en una decoloración mayor y significativa con el tiempo en comparación con el agua destilada y la Coca-Cola (P<0.05). Las resinas Tetric N Ceram (ΔE=7.0) y Tetric N Flow (ΔE=7.7) mostraron los valores más altos de cambio de color después de 30 días de inmersión en jugo de naranja. En este estudio se observó una decoloración por encima del umbral clínicamente aceptable (ΔE>2,7) para todos los materiales resinosos. Se puede especular que el jugo de naranja tiene un efecto más negativo sobre la estabilidad del color en comparación con la Coca-Cola. Además, la resina fluida fue más propensa a la decoloración que las resinas condensables.
En revista Odóvtos, vol. 24, no.2 (mayo-agosto 2022)
Descripción basada en el contenido visto el 19 de noviembre, 2024
También disponible en formato HTML y EPUB